Pelatihan Thaharah Dan Pengembangan Kreatifitas Anak Di Lembaga Kesejahteraan Sosial Anak Budi Mulia Plosoklaten Kediri - Siti Herni Nuraeni; Miftakhul huda (LP3M IAIFA Kediri, 2021)
The online Real Work Lecture Program (KKN) of the Faqih Asy'ari Islamic Institute is an activity program that is carried out online and minimizes field activities for students. The purpose of this online KKN program is to provide students with experience, knowledge, skills, and awareness of living in a community, as well as to prepare prospective undergraduates who are able to carry out online-based social change work. The theme of this research is â€œThararah Training and Child Creativity Development at the Budi Mulia Plosoelaten Child Welfare Institution (LKSA) in Kediriâ€. The purpose of holding these trainings in addition to children understanding and mastering education, especially in the religious field, besides that, it is also expected to be able to bring up creative ideas for children to always work. Furthermore, with the mastery of these insights and skills, orphanage children are better prepared to be independent, and become productive people. The type of method used in this report is the PAR (Participatory Action Research) method, which is a research that actively involves all relevant parties (stakeholders) in reviewing ongoing actions (where their own experience is a problem) in order to make changes and improvements towards better. The results of this online KKN activity program are proving that the program has been able to change the progress of the Budi Mulia orphanage children in terms of learning Islamic religious education, especially learning fiqh taharah which discusses ablution. In addition to understanding, they are also able to memorize prayers and practice them in each of the ablution movements according to the terms and conditions. And not only that they can also develop their creativity and abilities in various fields of art.